Critical survey of poetry [ British, Irish and Commonwealth poets - Reisman, Rosemary M. Canfield (Gale virtual reference library, 2011)
Profiles major poets throughout history and the world, including analyses of their significant individual poems or collections. This subset focuses on British, Irish, and Commonwealth poets